The Influence of Learning Arabic Vocabulary on Students' Reading Skills at Islamic Junior High School - Lolita, Nona; Al Rasyid, Harun (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to analyze the effect of learning Arabic vocabulary on reading skills in class VII students of MTs Madinatussalam Deli Serdang. The research method used is the quantitative method with a survey method approach by distributing questionnaires to 25 students. Then in the interferential analysis, a correlation coefficient test will be carried out using the product moment formula, the coefficient of determination, and the significance test of the correlation coefficient on learning Arabic vocabulary as variable X and reading skills as variable Y. The results of this study can be seen that there is an effect of learning Arabic vocabulary on reading skills in Class VII Students of MTs Madinatussalam. Where the lowest score of (Variable X) learning vocabulary is the lowest 60, and the highest score is 90, with a mean= of 77.8, median= 80, standard savings= 8.43, and mode= 77 and 85. Meanwhile, (variable Y) reading skill shows the value the lowest is 60 and the highest is 90, mean= 76.5, mode 80, median 79.5, standard deviation 7.67. So Efforts to improve learning Arabic vocabulary, a teacher must master several learning methods, as well as the ability to converse in Arabic and emphasize students memorizing vocabulary, increase Arabic vocabulary, provide motivation in Arabic both in learning and outside the classroom, and adequate facilities such as language labs.